2016
DOI: 10.1371/journal.pone.0147926
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Determinants of Chronic Non-Communicable Disease Risk Factors amongst Adults in the Dikgale Health Demographic and Surveillance System (HDSS) Site, Limpopo Province of South Africa

Abstract: BackgroundThe aim of the study was to determine the prevalence and determinants of chronic non-communicable disease (NCD) risk factors in a rural community in the Limpopo Province of South Africa.MethodsThis survey was conducted using the WHO "STEPwise approach to the surveillance of non-communicable diseases" (STEPS) methodology. Participants were residents of the Dikgale HDSS site and standardised international protocols were used to measure behavioural risk factors (smoking, alcohol consumption, fruit and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
122
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 109 publications
(140 citation statements)
references
References 40 publications
(51 reference statements)
14
122
4
Order By: Relevance
“…Obesity levels in this study are lower for both men and women when compared to an earlier study conducted in DHDSS [19]. Reasons for the difference between obesity levels are first, that the earlier study did not consider HIV infected people and second, age differences between to study samples.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Obesity levels in this study are lower for both men and women when compared to an earlier study conducted in DHDSS [19]. Reasons for the difference between obesity levels are first, that the earlier study did not consider HIV infected people and second, age differences between to study samples.…”
Section: Discussioncontrasting
confidence: 54%
“…This study is novel for the DHDSS site in that, unlike previous reports [15,19,36], the relationship between BMI and a pool of associated factors, is reported. Obesity levels in this study are lower for both men and women when compared to an earlier study conducted in DHDSS [19].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This result differs from the data from the STEPS survey in Benin in 2008, during which there was no association between HBP and the gender. We also noticed that obese people had a higher prevalence of HBP than non-obese, which was noted by other studies [23] [24] [25] [26]. Similarly, in our study, HBP was positively associated with total hypercholesterolemia and hyperglycemia; this finding is not surprising since HBP is often associated with other risk factors for cardiovascular disease.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have found women in low socioeconomic position to be less educated and to have poor access to nutrition [42]. Thus, they may be protected from the sedentary lifestyle that is adopted by those of high socioeconomic position.…”
Section: Discussionmentioning
confidence: 99%